Effect of oil palm empty fruit bunches (OPEFB) fibers to the compressive strength and water absorption of concrete - Adnan, Suraya Hani; Rusli, Nur Zakiah Hanim (Penerbit UTHM, 2017)
Growing popularity based on environmentally-friendly, low cost and lightweight building materials in the construction industry has led to a need to examine how these characteristics can be achieved and at the same time giving the benefit to the environment and maintain the material requirements based on the standards required. Recycling of waste generated from industrial and agricultural activities as measures of building materials is not only a viable solution to the problem of pollution but also to produce an economic design of building.